PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN SETS TERHADAP AKTIVITAS DAN HASIL BELAJAR FISIKA KELAS XI MIA-2 SMA NEGERI 3 SIBOLGA - Ferawati Artauli Hasibuan; Tetti Hasibuan (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The success of the world of education is determined by the quality of good learning. Successful learning can be seen from the increase in cognitive, affective, and psychomotor aspects. To improve the quality of learning, various learning models and the use of learning technology media are implemented. In this study, the learning model implemented is the SETS learning model (science, environment, technology, and society) by connecting technology with science and its implications for society and the environment. The purpose of this study was to determine how the effect of the implementation of the SETS learning model on the activities and learning outcomes of physics students in class XI MIA-2 SMA Negeri 3 Sibolga. This research was conducted using classroom action research (CAR) which consisted of 2 cycles and before the first and second cycles, the learning was carried out using the lecture method. From the results of the study, it was found that the student's learning activity in each cycle increased with the high category. The average value of students is 62.47 at the meeting with the lecture method. In the first cycle there was an increase of 6.81 points to 69.28 and in the second cycle there was also an increase of 9.36 points to 78.64. Students' learning mastery has increased from before SETS learning was carried out, from 32 students of class XI MIA-2 SMA Negeri 3 Sibolga it was found that the number of students who completed was 40.875%, increased in the first cycle to 65.625% and in the second cycle to 90.625%. Learning implementation SETS has a significant effect on increasing the activity and learning outcomes of physics class XII students of MIA-2 SMA Negeri 3 Sibolga which is applied in 2 cycles and observed in every meeting.